A study on relationship between attitude of households and the broadband acceptance: a case of household of capital city of Alor Setar, Kedah in Malaysia / Abdul Manaf Bohari and Zainal Md. Zan - Bohari, Abdul Manaf; Md. Zan, Zainal (Universiti Teknologi MARA, Perlis, 2011)
In general, an information and communications technology (ICT) adoption is importance initiatives in transforming the current status of socio-economy of people as well as contributes to the economic well being of nations. The studies and literature point of view has evolved to examine the impact of ICT on social-economic growth, as well as internet impact on daily social life of societies, includes in Malaysia. Currently, the broadband internet is being viewed as the most significant evolutionary step and always considered to be an innovation that will offer end users with fast access to new services, applications and digital content with latest real lifestyle and productivity benefits. On the one hand, previous research undertaken on the adoption of broadband internet has emphasized a demand perspective as well. Therefore, the examining of deployment of broadband it was found that such perspective is limited. The objective of this study is to identify the attitudes, subjective norm and perceived behavioural control factors that can influence adoption or rejection of internet broadband in the household sector. This study was conducted in the household area of Capital city of Alor Setar, Kedah as a study setting and sample selection will be determined by the convenience sampling method. At the end, this study will recommend some idea on how to increases the usage of broadband internet with specific to the household sector in Malaysia.